2022
DOI: 10.1111/1467-8500.12555
|View full text |Cite
|
Sign up to set email alerts
|

Where specialist and mainstream service systems collide: The National Disability Insurance Scheme in prisons

Abstract: The coordination of specialist with mainstream service systems is prone to role delineation and implementation difficulties worldwide. In the case of the National Disability Insurance Scheme (NDIS), this specialist/mainstream interface is complicated by federalism and funding responsibilities held by different levels of government. People with disability, especially cognitive or intellectual disability, are over-represented in Australia's prisons. Through semi-structured interviews with professionals working a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Smith‐Merry et al (2023) argue that addressing equity issues for Indigenous people requires whole‐of‐life case management from Indigenous‐controlled service providers. Other marginalised groups potentially disadvantaged through the scheme include women and girls (Yates, Carey, et al, 2021, 2022), people involved in the criminal justice system (Spivakovsky, 2021; Yates, Dodd, et al, 2022), people from culturally and linguistically diverse backgrounds (Senaratna et al, 2018); and people with psychosocial disabilities (Devine et al, 2022).…”
Section: Areas Of Debatementioning
confidence: 99%
See 1 more Smart Citation
“…Smith‐Merry et al (2023) argue that addressing equity issues for Indigenous people requires whole‐of‐life case management from Indigenous‐controlled service providers. Other marginalised groups potentially disadvantaged through the scheme include women and girls (Yates, Carey, et al, 2021, 2022), people involved in the criminal justice system (Spivakovsky, 2021; Yates, Dodd, et al, 2022), people from culturally and linguistically diverse backgrounds (Senaratna et al, 2018); and people with psychosocial disabilities (Devine et al, 2022).…”
Section: Areas Of Debatementioning
confidence: 99%
“…These insights are supported by research centring the experiences of people with disability: Olney et al (2022) found 'complex, disconnected and incomplete markets of services and supports' for people with disability without NDIS funding, and no evidence that Local Area Coordinators (an NDIS role originally intended to connect people with community supports) were assisting Tier 2 participants to access services. Research and non-peer reviewed literature also consistently demonstrates interface problems between the NDIS and mainstream services, without which the NDIS cannot function effectively (Yates, Dodd, et al, 2022). Consequently, the NDIS has been described as an 'oasis in the desert' of a wider disability support system that is not fit for purpose.…”
Section: Tier 2 and The 'Oasis In The Desert'mentioning
confidence: 99%
“…For formerly incarcerated people with disability, it is crucial that the NDIS works effectively with correctional services and yet there has been limited academic research exploring this intersection (see Young et al, 2017). Recent research suggests that both people with disability who are incarcerated and professionals working at the intersection of disability and criminal justice are uncertain about which services people in prison can access through the NDIS, leading to inconsistent practice (Yates et al, 2022, forthcoming).…”
Section: Introductionmentioning
confidence: 99%